Song and Music Information Systems as a Protection of Song Copyrights in Indonesia - Diana Silfiani (Jurnal Ilmiah Kebijakan Hukum, 2022)
The Indonesian government issues Regulation Government Number 56 of 2021 concerning Management Royalty Right Create Song and or Music as well as Regulation of the Minister of   Law and Rights basic Man Number 20 of 2021 concerning Regulation Implementation Regulation Government Number 56 of 2021 concerning Management Royalty Right Create Song and or Music as regulation implementation from Law No. 28 of 2014 concerning Right Create. One points urgent from second regulation the is mandate formation and development System Information Song and or Responsible music answer on administration and management royalty right create on songs and music used by users as a system integrated information. System Information Song and or Music is one effort government for give protection law on right create songs and music owned by creator. This post will use method study qualitative with approach descriptive comparing evaluation existence System Information Song and or Relative music new in Indonesia with practice international, in Thing this is United States of America as a country with industry music largest and commercialization. right create digital song has been recognized by wide.